2012
DOI: 10.1245/s10434-012-2318-2
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of a Positive-to-negative Change in Hormone Receptor Status after Neoadjuvant Chemotherapy in Patients with Hormone Receptor–positive Breast Cancer

Abstract: The switch of HR status after NCT is remarkable for HR-positive tumors. An HR-negative switch may identify patients who would benefit from alternative systemic therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
43
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 20 publications
6
43
2
Order By: Relevance
“…They found that the 5-year DFS and OS of patients whose tumors' HR status changed from positive to negative were significantly less than those of patients whose tumors remained HR-positive (P ¼ .003 and .001, respectively). 11 Our study, at a median follow-up of 40 months, found no significant differences in 5-year RFS or 5-year OS between patients whose tumors remained ER-positive and those whose tumors changed from ER-positive to ER-negative (P ¼ .89 and .28, respectively). We found a similar pattern among patients with and without changes in PR status.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…They found that the 5-year DFS and OS of patients whose tumors' HR status changed from positive to negative were significantly less than those of patients whose tumors remained HR-positive (P ¼ .003 and .001, respectively). 11 Our study, at a median follow-up of 40 months, found no significant differences in 5-year RFS or 5-year OS between patients whose tumors remained ER-positive and those whose tumors changed from ER-positive to ER-negative (P ¼ .89 and .28, respectively). We found a similar pattern among patients with and without changes in PR status.…”
Section: Discussioncontrasting
confidence: 52%
“…8 Few studies have investigated the association between biomarker status alterations and long-term outcomes, finding inconsistent results. [9][10][11] Furthermore, little is known about the relationship between alterations in receptor status after NCT and long-term survival outcomes. 12 The objectives of this study were to assess the frequency of ER, PR, and HER2 status changes and changes in breast cancer subtypes after NCT and to determine whether these changes were correlated with long-term survival outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Hirata et al [29] recently reported that after adjuvant hormone therapy, the survival of patients whose HR status had changed (either positively or negatively) in the resection specimen after NACT did not differ from that of patients whose HR status remained positive after NACT. By contrast, Chen et al [30] reported that following adjuvant hormone therapy, the survival of patients whose HR status changed after NACT was poorer than that of patients whose HR status remained positive after NACT.…”
Section: Discussionmentioning
confidence: 99%
“…found that the positive-to-negative change in hormone-receptor status after neoadjuvant chemotherapy was an independent predictor of poor survival. 12 Other studies found that cases with discordant receptor status of metastatic disease and primary breast cancer have a worse prognosis than those with ER concordant-positive status. 13-15 …”
Section: Introductionmentioning
confidence: 98%